Presentation - Cupe Calcina, Eloy Marcelo (2022)
We are pleased to present the fifth issue of Ius Vocatio. Research Journal of the Superior Court of Justice of Huanuco, an intellectual organ that has persisted in its continuity and academic rigor, despite the difficulties that institutions, such as the Judiciary and the Superior Court of Justice of Huanuco, have faced due to the health and economic crisis caused by the pandemic of COVID-19, a situation that in this 2022 we are overcoming as a country. This year is also important for the journal, since the periodicity of the same is from now on biannual, which does nothing but boost our professional commitment that we perform for this noble mission of disseminating the academic work of our judicial servants, who promote research in the various fields of law.